Beitrag zur Kenntnis der Bienengattung Andrena Fabricius in Griechenland. - Warncke, Klaus (Contributions to Entomology = Beiträge zur Entomologie, 1965)
There is recorded a total of 136 species of the genus Andrena F. (Hymenoptera, Apidae) occuring in Greece, including the relative synonymy. The following species and subspecies respectively are described: A. magna, A. athenensis, A. flavobila. A. schmiedeknechti Magr. ssp. flavopilis, A. minapalumboi Grib. ssp. delphiensis. A. tscheki Mor. ssp. tritica, A. serraticornis, A. taraxaci Gir. ssp. orientana. A. cineophila. A. humabilis. A. urdula, A. larisana, A. balcanica, A. unicincta Fr. ssp. westensis, A. muscaria. A. glidia, A. langadensis, A. trikalensis. A. forsteri, A. crassana, A. gamskrucki, A. alfkenelloides, A. paganettina, A. rugothoraee, A. dargia, A. corpana, A. magunta, A.tenuicula Stöckhert ssp. lamiana, A. helenica, and A. bulgariensis. A. cyanescens var. rufescens Friese as a homonym of A. rufescens Perez required, a new name: A. curvana. A. strymonia Pittioni female nес male was named new as A. graecella Furthermore A. abbreviata Dours is redescribed and defined by means of lectotype selection. Nomenclatural Actsabbreviata Dours, 1873 (Andrena), Lectotypeafkenelloides Warncke, 1965 (Andrena), spec. n.athenensis Warncke, 1965 (Andrena), spec. n.balcanica Warncke, 1965 (Andrena), spec. n.bulgariensis Warncke, 1965 (Andrena), spec. n.cinereophila Warncke, 1965 (Andrena), spec. n.corpana Warncke, 1965 (Andrena), spec. n.crassana Warncke, 1965 (Andrena), spec. n.curvana Warncke, 1964 (Andrena), nom. n. pro Andrena cyanescens, var. rufescens Friese, 1922, nec Perez, 1895dargia Warncke, 1965 (Andrena), spec. n.flavobila Warncke, 1965 (Andrena), spec. n.forsteri Warncke, 1965 (Andrena), spec. n.gamskrucki Warncke, 1965 (Andrena), spec. n.glidia Warncke, 1965 (Andrena), spec. n.graecella Warncke, 1965 (Andrena), nom. n. pro Andrena strymonia Pittioni, 1950 (female), nec malehelenica Warncke, 1965 (Andrena), spec. n.humabilis Warncke, 1965 (Andrena), spec. n.langadensis Warncke, 1965 (Andrena), spec. n.larisana Warncke, 1965 (Andrena), spec. n.magna Warncke, 1965 (Andrena), spec. n.magunta Warncke, 1965 (Andrena), spec. n.muscaria Warncke, 1965 (Andrena), spec. n.paganettina Warncke, 1965 (Andrena), spec. n.rugothorace Warncke, 1965 (Andrena), spec. n.serraticornis Warncke, 1965 (Andrena), spec. n.tomora Warncke, 1965 (Andrena), spec. n.trikalensis Warncke, 1965 (Andrena), spec. n.urdula Warncke, 1965 (Andrena), spec. n.delphiensis Warncke, 1965 (Andrena minapalumboi), sspec. n.flavopiles Warncke, 1965 (Andrena schmiedeknechti), sspec. n.orientana Warncke, 1965 (Andrena taraxaci), sspec. n.lamiana Warncke, 1965 (Andrena tenuicula), sspec. n.tritica Warncke, 1965 (Andrena tscheki), sspec. n.westensis Warncke, 1965 (Andrena unicincta), sspec. n.